2016
DOI: 10.1017/jog.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

A flow cytometric method to measure prokaryotic records in ice cores: an example from the West Antarctic Ice Sheet Divide drilling site

Abstract: ABSTRACT. Microorganisms were the earliest inhabitants on our planet that occupy nearly every environment, and play a major role in biogeochemical cycles. Despite their global importance, there remains a paucity of data on microbial responses to long-term environmental and climatic changes. Microorganisms are known to be immured in glacial ice, but no high-resolution temporal records of their density exist, owing in large part to the lack of appropriate clean methodology that allows for rapid analysis of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 126 publications
(197 reference statements)
0
17
0
Order By: Relevance
“…A series of duplicated cultures was established for each isolated bacterial strain using four culturing temperatures (4°C, 8°C, 12°C, and 25°C) and four NaCl concentrations in the culturing media (0.2, 0.5, 0.7, and 0.9 M). Cell concentrations were monitored over time using a PhytoCyt flow cytometer (Turner Designs) with SYBR Green I (Molecular Probes) staining following the protocol described in Santibáñez et al ().…”
Section: Methodsmentioning
confidence: 99%
“…A series of duplicated cultures was established for each isolated bacterial strain using four culturing temperatures (4°C, 8°C, 12°C, and 25°C) and four NaCl concentrations in the culturing media (0.2, 0.5, 0.7, and 0.9 M). Cell concentrations were monitored over time using a PhytoCyt flow cytometer (Turner Designs) with SYBR Green I (Molecular Probes) staining following the protocol described in Santibáñez et al ().…”
Section: Methodsmentioning
confidence: 99%
“…To assess reproducibility and identify potential carryover by the melter system, we melted and analyzed parallel replicate sections of the ice core that corresponded to 4% of our target ice‐core section (1,764–2,709 m). The replicate sections were melted days or months later than the original sections for analysis and did not show significant differences from the adjacent samples (Santibáñez et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…We used flow cytometry in concert with a continuous melting system (Santibáñez, McConnell, & Priscu, ) to produce the first temporal record of prokaryotic (nonphotosynthetic members of the domains Bacteria and Archaea ) cell concentration from a deep West Antarctic ice core (Buizert et al., ) spanning from 27,000 to 9,600 year before present (27 to 9.6 ka BP). Together with other high‐resolution measurements made on the same ice core, we described the temporal trends and patterns of the prokaryotic record with respect to past climatic events and evaluated the potential atmospheric sources (e.g., plants, soils, water, and rocks (Edmonds, ; Jones & Harrison, ; Kuhlman, Venkat, La Duc, Kuhlman, & McKay, ) for the prokaryotic cells comprising the record.…”
Section: Introductionmentioning
confidence: 99%
“…O nce considered inhospitable to life, in recent decades icy environments on Earth have been found that preserve organic material and even harbor active microbial communities (Priscu et al, 1998(Priscu et al, , 1999Siegert et al, 2001;Priscu, 2005;Santibáñez et al, 2005Santibáñez et al, , 2018Krembs et al, 2011;Uhlig et al, 2015). Glacial ice on Earth is known to contain organic material (Barnes et al, 2003;Barletta et al, 2012), including bacteria, algae, viruses, plant fragments, pollen grains, and black carbon.…”
Section: Introductionmentioning
confidence: 99%